Otitis externa in the dog and the eat - KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Otitis externa is the most common disorder of the cat ear canal in small animals, with a higher incidence in dogs than in cats. It has a multifactorial etiology comprising of numerous predisposing, primary and perpetuating factors. The most important primary causes are atopy, food allergy, otodectic mange, foreign bodies, endocrinopathies and keratinisation disorders. Bacteria and yeasts residing in the ear canal usually complicate the initial lesions thus leading to the establishment of ceruminous or suppurative otitis externa. Otitis media and chronic hyperplastic changes of the ear canal are hold responsible for the perpetuation of the disease. A diagnosis is easily made from the history, the cleaning of the ear canal and otoscopy, the cytologic and parasitologic examination of ear exudates, the bacterial culture and sensitivity testing and the radiography (cartilage mineralization, otitis media). Evaluation and treatment of the underlying skin disease is always necessary. Therapy of otitis externa depends on identifying and controlling the predisposing and primary factors, whenever possible. Medical treatment includes cleaning of the ear canals and the middle ear, applying topicals and/or administering systemic medications (acaricides, antifungal agents, antibiotics, glucocorticoids). Corrective surgeries are indicated in the refractory to medical treatment cases.